2021
DOI: 10.1002/ejp.1715
|View full text |Cite
|
Sign up to set email alerts
|

Dependence‐like behaviour in patients treated for medication overuse headache: A prospective open‐label randomized controlled trial

Abstract: Background Dependence‐like behaviour may complicate withdrawal and increase risk of relapse of medication overuse headache (MOH). The most effective treatment for reducing dependence‐like behaviour is unknown. Objectives To compare patient‐reported outcomes among three treatment strategies for MOH. The primary outcome was change in Severity of Dependence Scale (SDS) score from baseline to 6 months. Methods Patients with MOH were randomized to (1) withdrawal combined with preventive medication from start (W+P),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Although our hypothesis was that the treatment strategy including withdrawal with immediate preventive treatment would have the largest treatment effect, all three strategies proved equally effective after 1 year. However, as previously reported, the combination of withdrawal and preventive medication from the start led to the fastest improvement within the first 6 months, based on the number of patients with resolved MOH and number of patients reverting to episodic headache 6,7 . The most important message from this 1‐year follow‐up study is that this rapidly obtained effect in the W+P group is a long‐lasting and stable treatment effect.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Although our hypothesis was that the treatment strategy including withdrawal with immediate preventive treatment would have the largest treatment effect, all three strategies proved equally effective after 1 year. However, as previously reported, the combination of withdrawal and preventive medication from the start led to the fastest improvement within the first 6 months, based on the number of patients with resolved MOH and number of patients reverting to episodic headache 6,7 . The most important message from this 1‐year follow‐up study is that this rapidly obtained effect in the W+P group is a long‐lasting and stable treatment effect.…”
Section: Discussionsupporting
confidence: 68%
“…There were no deviations from the original trial protocol, which is found in Supporting Information . Results from baseline to 6‐month follow‐up have already been published 6,7 . This paper focuses on the planned secondary analyses on outcomes after 1 year.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations